Comparison of Left Ventricular Ejection Fraction in Heart Failure Patients on Echocardiography, Cardiac Magnetic Resonance Imaging and Single Photon Emission Computed Tomography - Ahmed, Iftikhar; Nadeem, Asif; Saeed, Nazish; Shiram, Syed Ali; Hussain, Zahid; Tariq, Muhammad Naeem; Kamran, Javeria; Mustafa, Attiya; Azad, Naseem; Shahzad, Syed Khurram (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the left ventricular ejection fraction on echocardiograph, cardiac magnetic resonance imaging and single-photon emission computed tomography scan in heart failure patients.Study Design: This was a prospective cross-sectional study.Place and Duration of Study: Tertiary Cardiac Care Center of Rawalpindi, Pakistan, from Nov 2021 to Apr 2022.Methodology: This was a prospective cross-sectional study conducted from November 2021 to April 2022 at a tertiary cardiac care center of Rawalpindi. Thirty (n=30) heart failure patients of either gender with reduced ejection fraction were selected by consecutive sampling technique and were analyzed to quantify their left ventricular ejection fraction (LVEF) using Echo, CMR and SPECT scan. All three modalities were used to measure LVEF in these patients and were compared accordingly.Results: The LVEF measured by Cardiac Magnetic Resonance Imaging, Single Photon Emission Computed Tomography Scan and Echocardiography was in the range of 15% to 67%. The mean LVEF was 37.2±14.2 by CMR, 37.17±14.1 by SPECT and 38±12.3 by Echo. The mean LVEF determined by SPECT was slightly lower while that determined by Echocardiography was slightly higher. The measured p-value of LVEF by the three modalities, however, indicated statistically difference (p-value